Językowy obraz aborcji i opozycji płód – dziecko: Analiza leksykalna tekstów prasowych w mediach elektronicznych w pierwszym dwudziestoleciu XXI wieku (lata 2000–2018) - Szczepkowska, Małgorzata (Ochrona życia ludzkiego na prenatalnym etapie rozwoju: Aspekty społeczne, medyczne i prawne, 2024)
The subject of the article is a qualitative and quantitative analysis of abortion vocabulary excerpted from news and journalistic articles published in the electronic media in the first two decades of the 21st century. The study showed that in the discourse on abortion there is a clear fetus–child opposition, which results from granting or not granting the nasciturus the status of a human being. On the basis of this opposition, two separate linguistic repertoires are built, and using them places the speaker on one side of the ideological dispute. The article also argues with the findings of other researchers dealing with the subject of abortion-related vocabulary. The key conclusion from the analysis concerns the linguistic image of the nasciturus and may be surprising in connection with the theses of pro-abortionists, according to whom it is an abuse to talk about the nasciturus as a child. A comparison of press texts dealing with abortion with articles dealing with the subject of pregnancy, motherhood or miscarriage itself shows that in all (taken together) texts concerning the prenatal stage of human development, the nasciturus is called a child more than three times more often than a fetus. This, in turn, means that the child is the main name for the unborn being, while the linguistic status of the nasciturus as a person or a non-person, even in the left-liberal press, depends on the context in which it is spoken of (a child in texts about pregnancy or miscarriage, a fetus in texts about abortion).